2019
DOI: 10.1039/c8ra10494h
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced catalytic activity of Au core Pd shell Pt cluster trimetallic nanorods for CO2 reduction

Abstract: Au@Pd@Pt nanorods greatly enhance the catalytic activities for CO2 reduction because of Pd–Pt edge active sites as investigated by SERS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…10 Alternatively, the electrochemical reduction of CO 2 can proceed in ambient environments and is capable of producing a variety of hydrocarbons with high selectivity. 3,[11][12][13] Various electrocatalysts, including composites containing transition metals 14 such as Au, 15 Ag, 16,17 Fe, 18 Co, 19,20 Sn, 21 Pd, 22,23 and Ni 24 have been proposed to improve the yield of the electrochemical reduction of CO 2 . In addition to those, a variety of Cu-based nanocatalysts can also enhance the electrochemical formation of hydrocarbons from CO 2 -saturated aqueous solutions and do so at ambient temperature and pressure.…”
Section: Introductionmentioning
confidence: 99%
“…10 Alternatively, the electrochemical reduction of CO 2 can proceed in ambient environments and is capable of producing a variety of hydrocarbons with high selectivity. 3,[11][12][13] Various electrocatalysts, including composites containing transition metals 14 such as Au, 15 Ag, 16,17 Fe, 18 Co, 19,20 Sn, 21 Pd, 22,23 and Ni 24 have been proposed to improve the yield of the electrochemical reduction of CO 2 . In addition to those, a variety of Cu-based nanocatalysts can also enhance the electrochemical formation of hydrocarbons from CO 2 -saturated aqueous solutions and do so at ambient temperature and pressure.…”
Section: Introductionmentioning
confidence: 99%
“…As for Pd, previous research has found that Pd can convert CO 2 into formic acid, but the in situ formed CO as the main byproduct during the reaction process is inevitably adsorbed on the catalytic active site of the Pd surface, which hinders the continuous reactions to further produce multi-carbon products [ 26 , 27 ]. Nevertheless, recent research has proved that alloying Pd with other metals can effectively upgrade its CRR activities and CO tolerance [ 28 , 29 , 30 , 31 , 32 ]. However, due to the symmetrical linear structure of the CO 2 molecule and the highly uniform density of the electronic state of the whole molecule, CO 2 is hardly adsorbed on the active sites of the catalysts with a bent configuration.…”
Section: Introductionmentioning
confidence: 99%
“…There is a sudden drop in the current from a value J 0 to J 1 followed by a gradual decrease over a time period of 60 s to a stable value J ∞ . 42,43 The sudden drop can be attributed to the instantaneous loss of action of photogenerated carriers; on the other hand, the gradual recovery is due to a gradual evolution from the photothermally heated conditions at the interface to the dark thermal conditions. Therefore, the ratio of the contribution of photogenerated carriers to that of the photothermal effect on the enhancement in current is given by (J 1 − J 0 )/(J ∞ − J 0 − J 1 ), which is estimated to be roughly 70:30 for CuPtNi 0.23 / CNT.…”
mentioning
confidence: 99%